USE OF PICTURE AND PICTURE METHOD IN INCREASING ABILITY OF SUNWARE STUDENTS - Marta Indri Hapsari (STKIP Siliwangi, 2017)
The main issues of this research is how to improve the ability of elementary school students (ES) in recognizing the sun through picture and picture method. The objectives of the research are as follows: (1). Improving the ability of elementary students in recognizing the sun through picture and picture method; (2). Provide learning through picture and picture method that improves students' ability. The methods / approaches used in achieving the following objectives: (a). Collect students and elementary teachers involved in research; (B). Provide an overview of the research activities to be undertaken; (C). Reflecting, discussing about learning with picture and picture method; (D). Collaborate with elementary teachers in the determination of experimental class and control class; (E). Implementation of learning method picture and picture; (F). Evaluation of learning with picture and picture method. The results showed that there is an increase in the ability of elementary students in recognizing the sun through the study of picture and picture method by 19%; (2). Elementary students are enthusiastic about learning the picture and picture method given by the teacher.  Keywords: Method, Learning, Picture and picture